ANALISIS ERGONOMI TERHADAP KONDISI INTERAKSI MANUSIA-MESIN MELALUI PENDEKATAN PARTISIPATORI PADA BENGKEL KAYU JURUSAN TEKNIK SIPIL POLITEKNIK NEGERI BALI (PNB) - Sudiajeng, Lilik; Oesman, Titin Isna; Sutopo, Nyoman (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2011)
Woodworking industries is one of the funding resources of Indonesia. Mechanization was done but less awareness of occupational safety and health, so there were still high risk of occupational accidents and diseases. One of the main problems was man-machine interaction. Research was conducted at the woodworking workshop Bali State Polytechnic with 13 students as participants. It was a participatory research with one group pre and post test design. Result showed that the clearance among machines was about 1.2 – 1.5 m, while the shoulder width and the distance of spreading arms’ participants were 0.52 m and 1.825 m (percentile-95). The terminal blade of radial saw was 30.5 cm out of reach limit (percentile-5). In addition, the terminal ankle blade of drilling machine was 36.5 cm out of reach limit (percentile-5). Participants got complains for the right shoulder (76.92%), left shoulder (69.23%), the right and left hips (61.54%) and low back (53.85%). In similarities, 54.62% of participants got weakened activities, 44.62% got weakened motivation and 68.46% got physically fatigue. In conclusion, the man-machine interaction was not harmony and caused musculoskeletal complain and fatigue. It is needed the improvement of work condition to protect the workers’ safety and health.